Online databases on Quranic handwritten words - Abuzaraida, Mustafa Ali; Zeki, Akram M.; Zeki, Ahmed M. (Little Lion Scientific Islamabad Pakistan, 2014)
In this paper, an online Arabic handwritten words database is presented to be the first online Quranic handwritten words dataset. The dataset was collected naturally using Acer computer tablet 1.5 GHz core i3 by writing the words on a smooth touch screen using a special pen stylus. Here, a platform interface was designed to collect the handwritten words using Matlab environment. Handwritten words were chosen as the most common words repeated in the holly Quran. The initial version of (Quranic Handwritten Words) QHW database includes 120 handwritten words and divided equally into two sets to be written by 200 writers in total. The QHW database contains 12000 sample including more than 42,800 characters and 23,300 sub words. Handwritten words were mainly written by variety of people aged between 6 and 50 years from several countries. The main aim of creating this database is to be used in an online Arabic recognition system and make it available to other researchers while there is no public database can be use nowadays. Also, Some preprocessing steps those applied to standardize the all words of this database are presented in this paper.